Legal Analysis of Law Enforcement in Handling Anarchist Demonstrations in Cirebon City - Sukatendel, Reggy Permana; Hafidz, Jawade (UNISSULA Semarang, 2025)
Abstract. Demonstration or protest is a right to express opinions that is guaranteed in the democratic country of Indonesia, however, in conducting demonstrations or protests must use procedures that uphold morality and good ethics. Anarchic demonstrations not only deviate from the meaning of democracy but can also cause problems for the affected community. This study aims to analyze and describe the implementation mechanism of handling anarchist demonstrations in Cierbon City at this time. To analyze and describe the obstacles and solutions in efforts to realize legal balance in handling anarchist demonstrations in Cierbon City.The type of legal research used is non-doctrinal. Based on the research results it is known that. The problems that hinder the optimization of handling anarchist demonstrations consist of the lack of regulation of the categorization of anarchist actions in demonstrations as a type of criminal act. In law enforcement, the problem is the lack of police personnel and infrastructure in handling anarchist demonstrations which are often in large groups. The public view is that anarchist actions in demonstrations are included in the category of the right to express opinions. A solution to overcome the problems that hinder the optimization of handling anarchist demonstrations is to make regulations in the Criminal Code specifically related to anarchist demonstrations as a crime. The police need to increase the number of personnel and infrastructure related to the task of handling anarchist demonstrations. There needs to be education for the public that anarchist actions do not reflect a civilized and democratic attitude, but are actions that are contrary to democratization in the implementation of demonstrations.